FAKTOR DOMINAN YANG BERHUBUNGAN DENGAN PERILAKU PEMERIKSAAN PAP SMEAR PADA WANITA USIA SUBUR - Salmah Salmah; Wahyudin Rajab; Eha Djulaeha (Poltekkes Kemenkes Jakarta III, 2013)
Cancer of Serviks is the deadly disease that has an effect in the woman healthy on the world and the first rank in the cancer case that attack the woman. In Asia, there is 266.000 new case of cancer of serviks that is diagnosed every year(Singso,2006). Meanwhile, the death caused by estimated reached 233.400 cases every year (WHO.2002). The right Medical treatment will help to stop the abnormal cells of the cancer of serviks that can be detected with a test called